The prognostic value of positron emission tomography performed after two courses (INTERIM‐PET) of standard therapy on treatment outcome in early stage Hodgkin lymphoma: A multicentric study by the fondazione italiana linfomi (FIL). Issue 6 (10th May 2015) - Rigacci, Luigi; Puccini, Benedetta; Zinzani, Pier Luigi; Biggi, Alberto; Castagnoli, Antonio; Merli, Francesco; Balzarotti, Monica; Stelitano, Caterina; Spina, Michele; Vitolo, Umberto; Stefoni, Vittorio; Levis, Alessandro; et al.
<x xml:space="preserve">Abstract</x> This retrospective study included 246 patients with a new diagnosis of Hodgkin Lymphoma (HL) with a localized‐stage (IA‐IIA), consecutively admitted from January 2002 to December 2008, by twelve Italian hematological centers on behalf of Fondazione Italiana Linfomi (FIL). Patients were staged at baseline and after two cycles of chemotherapy with PET. All patients were treated with four cycles of ABVD followed by involved‐field radiotherapy. No treatment change, based on PET‐2 results was allowed. Endpoint of the study was the predictive role of PET‐2 on 2‐y failure‐free survival (FFS). PET‐2 was positive in 36 patients (15%) and negative in 210. After a mean follow‐up of 46 (3–105) months 19/36 PET‐2 positive patients progressed or relapsed and 17 achieved and maintained a CCR. The positive and negative predictive value of a PET2 was 53% and 95%, respectively. The sensibility, specificity and accuracy of PET2 were 65.5%, 92% and 89%, respectively. PET‐2 positive scans were centrally reviewed according to the recently defined Deauville Criteria. Upon review the PPV and NPV was 73% and 96% overall. Factors with prognostic significance for progression in univariate analysis were a positive PET‐2 (P = 0.000) and the presence of bulky disease (P < 0.01). In a multivariate analysis the only factor that affected negatively FFS was a positive PET‐2 (P = 0.000). This study confirms that interim‐PET could be considered a prognostic test also in early stage HL, but is unlikely to be a factor that will justify the change of therapeutical approach. Am. J. Hematol. 90:499–503, 2015. © 2015 Wiley Periodicals, Inc.